2010
DOI: 10.1038/ejhg.2010.106
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical and factual willingness to participate in biobank research

Abstract: In the debate on biobank regulation, arguments often draw upon findings in surveys on public attitudes. However, surveys on willingness to participate in research may not always predict actual participation rates. We compared hypothetical willingness as estimated in 11 surveys conducted in Sweden, Iceland, United Kingdom, Ireland, United States and Singapore to factual participation rates in 12 biobank studies. Studies were matched by country and approximate time frame. Of 22 pairwise comparisons, 12 suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
93
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 27 publications
2
93
3
1
Order By: Relevance
“…Additionally, all the genome studies were conducted at BCM in Houston, Texas within the Texas Medical Center, a highly respected institution in the area. These factors could have influenced their decision to participate and to release their data as other studies have noted the influence of trust on willingness to participate in genetic research [24,30,31]. Trust was significantly associated with participants’ privacy-utility determination as those who expressed some to high trust more often selected advancing research as more important than privacy protection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, all the genome studies were conducted at BCM in Houston, Texas within the Texas Medical Center, a highly respected institution in the area. These factors could have influenced their decision to participate and to release their data as other studies have noted the influence of trust on willingness to participate in genetic research [24,30,31]. Trust was significantly associated with participants’ privacy-utility determination as those who expressed some to high trust more often selected advancing research as more important than privacy protection.…”
Section: Discussionmentioning
confidence: 95%
“…While public opinion data provides valuable insight into general attitudes toward genetic research, this may not necessarily reflect the views of actual genome research participants. A review of 22 studies comparing actual to hypothetical willingness found studies reported more actual participation than suggested in hypothetical survey findings [24]. The authors provide a psychological explanation that these survey respondents may not be as emotionally invested as real research participants.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, research experience has found incongruence between the stated willingness to donate a biological sample and the actual participation rates in genetic research (Johnsson et al 2010). Studies around the world often find at least 80 % of people state that they are willing to donate biological material for research purposes (Wendler 2006;Sanderson et al 2013); however, the actual participation rates for genetic and biobank research can be closer to half of the rate of reported willingness (Johnsson et al 2010), although some efforts have had high actual participation (McQuillan et al 2003). In studies recruiting from general population or community samples, participation rates are lower when a consent form mentions the study of genes and DNA (Matsui et al 2005;McQuillan et al 2006;Melas et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, we found a wider range for actual baseline participation rates. This may be due to the substantial difference between hypothetical and actual consent to participate in a biobank study [65]. Different factors may play a role in deciding whether to participate in a hypothetical or actual biobank study.…”
Section: Discussionmentioning
confidence: 99%